Detection of phosphorylation status of cytokinetic components - Meitinger, Franz; Palani, Saravanan; Pereira, Gislene (Yeast Cytokinesis, 2016)
Yeast cells can be easily cultured, synchronized, and genetically modified making them a convenient model system to study molecular mechanisms underlying cytokinesis. Here, we describe simple methods that allow the analysis of the phosphorylation profile of cytokinetic proteins, both in vivo and in vitro, using standard laboratory equipment. In addition, we compare the ability of three different, standard, and optimized acrylamide gel conditions to separate phosphorylated forms, using the protein Inn1 as an example.